A systematic review: differentiation of stem cells into functional pericytes. Issue 5 (24th January 2017) - Xu, Jianguang; Gong, Ting; Heng, Boon Chin; Zhang, Cheng Fei
ABSTRACT: Pericytes are an integral cellular component of vascular structures. Numerous studies have investigated various stem cell types as potential sources of pericytes for application in cell‐based therapy. The diverse stem cell types and variable experimental protocols of these studies make it imperative to evaluate the relevant scientific literature on the basis of a unified standard. The purpose of this systematic review is to rigorously evaluate the relevant scientific literature for conclusive evidence that stem cells can differentiate into functional pericytes. An online literature search was conducted up to July 2016. Eligible papers were evaluated on 4 pertinent criteria: 1) appropriate controls, 2) markers to confirm pericyte phenotype, 3) techniques for assessing pericyte functionality, and 4) differentiation efficiency of the protocol. Our search yielded 20 eligible studies (from 2006 to 2016), 12 of which were published in the past 5 yr. Of these 20 articles, only 1 had positive control, and 5 papers evaluated differentiation efficiency. The most commonly used pericyte markers were neuron‐glial antigen 2, platelet‐derived growth factor receptor‐β, and α‐smooth muscle actin. Three articles were associated with adipose stem cells, 4 with mesenchymal stem cells, and 7 with pluripotent stem cells, whereas the remaining 6 articles were based on other miscellaneous stem cell types. Stem cells can serve as a potential source of pericytes, but there should be standardized guidelines in future studies for assessing pericyte differentiation.—Xu, J., Gong, T., Heng, B. C., Zhang, C. F. A systematic review: differentiation of stem cells into functional pericytes. FASEB J. 31, 1775–1786 (2017). www.fasebj.org